Distinct leaf functional traits of Tamarix chinensis at different habitats in the hinterland of the Taklimakan desert - Tayir, Mawlida; Dai, Yue; Shi, Qingdong; Abdureyim, Anwar; Erkin, Flora; Huang, Wanyuan (Frontiers in Plant Science, 2023)
ABSTRACT: Leaf functional traits reflect plant adaptive strategies towards environmental heterogeneity. However, which factor play the key role of plasticity of leaf functional traits among various variable environmental factors remains unclear in desert hinterland oasis area. Here, we analyzed variations in leaf water content (LWC), δ13C values of leaves (δ13C), specific leaf area (SLA), leaf organic carbon concentration (LOC), leaf total nitrogen concentration (LTN), leaf total phosphorus concentration (LTP), and leaf C: N: P stoichiometry in Tamarix chinensis growing in five habitats at the Daliyabuyi, a natural pristine oasis in northwestern China, that differ abiotically and biotically. The spatial heterogeneity of leaf functional traits was evident. Abiotic factors vitally influence leaf functional traits, of which groundwater depth (GWD) and soil C: N stoichiometry (SOC: STN) are crucial. GWD exhibited close relationships with LWC (P < 0.05) and LOC: LTP (P < 0.01), but not δ13C. Soil water content (SWC) and SOC: STN were negatively related to SLA (P < 0.01; P < 0.05). While, SOC: STN showed positive relationships with LOC: LTN (P < 0.05). As for biological factors，we found T. chinensis in habitat with Sophora alopecuroidies had the highest LTN, possibly as a result of N fixation of leguminous plants (S. alopecuroidies) promotes the N concentration of T. chinensis. Close relationships also existed between leaf functional traits, LWC showed significantly negatively relatd to δ13C, LOC: LTN and LOC: LTP (P < 0.05), whereas δ13C had positively correlated with LOC: LTN (P < 0.01) but negatively correlated with LTN (P < 0.05). T. chinensis had relative higher LWC couple with lower δ13C, and exhibiting lower C, N, P in leaves and their stoichiometric ratios, and also lower SLA which compared with other terrestrial plant. Such coordinations suggesting that T. chinensis develops a suite of trait combinations mainly tends to more conservative to response local habitats in Daliyabuyi, which is contribute to understand desert plant resource acquisition and utilization mechanisms in extremely arid and barren environments.